The effect of physical activity breaks, including motor-cognitive coordination exercises, on employees' cognitive functions in the workplace. - Buuck, Sabine; Voll, Stefan; Jansen, Petra (Work, 2023)
BACKGROUND: The findings of the effectiveness of physical activity on adults' cognitive abilities have not yet been transferred into corresponding fields of application. OBJECTIVE: The present study evaluates a motor-cognitive coordination programme in a company to improve employees' cognitive performance in the short and medium term. METHODS: A total of 67 employees — 32 men and 35 women aged between 19 and 61 years — participated in this study, and 55 completed the study. The sample was randomly divided into an experimental group, which received a motor-cognitive coordination training, and a control group, which received a relaxation and mobility training. Both groups met for 15-minute sessions three times a week for eight weeks. Before and after the intervention, working memory, attention, information-processing capacity, divergent thinking, and mood were measured. In addition, acute effects regarding attention and mood were tested. RESULTS: The results showed that the motor-cognitive coordination break improves working memory and divergent thinking after eight weeks of intervention, whereas neither the mood nor the information processing speed improved more for the experimental group compared to the control group. The results on the acute increase in attention performance failed to reach significance. CONCLUSION: The new approach of this study was not only the derivation and development of targeted exercises, but also their testing and evaluation in the field of application. Motor-cognitive coordination exercise in the workplace might play an important role in both occupational health management and personnel development, especially for companies that are under highly competitive and innovative pressure.